Analysis of Reticulocyte Hemoglobin Equivalent in Routine and Non-Routine Blood Donors in Makassar - Andy Inna Agustina; Samad R; Juliyani S; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Blood donation often causes the depletion of iron stores in the body resulting in anemia. One of the markers to assess the hemoglobin content in reticulocytes is Ret-He. This study aims to analyze Ret-He in routine and non-routine blood donors. This was a cross-sectional study using primary data from routine and non-routine blood donors at the Blood Transfusion Technical Implementation Unit of South Sulawesi Province from June 2021 to September 2021. The study population was blood donors who met the donor selection requirements. The research samples were blood donors who qualified as routine and non-routine blood donors. For a total of 66 blood donors, namely 33 routine blood donors and 33 non-routine blood donors, the mean Ret-He of routine blood donors (33.6 pg) was lower than that of non-routine blood donors (35 pg). The Mann-Whitney test showed a significant difference between routine and non-routine blood donors (p=0.008). Ret-He levels in routine blood donors were significantly lower than in non-routine blood donors. This is because routine blood donors donate blood more frequently and regularly, affecting the iron reserves in the donor's body. The study showed that the Ret-He level of routine blood donors was lower than that of non-routine blood donors but was still within the normal values of Ret-He (normal value: 30.2 pg - 36.7 pg). Ret-He levels in routine blood donors were lower than non-routine blood donors but were still within the normal range.